Asset Pricing with Optimal Under-Diversification - Elenev, Vadim,Landvoigt, Tim (National Bureau of Economic Research, 2023)
We study sources and implications of undiversified portfolios in a production-based asset pricing model with financial frictions. Households take concentrated positions in a single firm exposed to idiosyncratic shocks because managerial effort requires equity stakes, and because investors gain private benefits from concentrated holdings. Matching data on returns and portfolios, we find that the marginal investor optimally holds 45% of their portfolio in a single firm, incentivizing managerial effort that accounts for 4% of aggregate output. Investors derive control benefits equivalent to 3% points of excess return, rationalizing low observed returns on undiversified holdings in the data. A counterfactual world of full diversification would feature higher risk free rates, lower risk premiums on fully diversified and concentrated assets, less capital accumulation, yet higher consumption and welfare. Exposure to undiversified firm risk can explain approximately 40% of the level and 20% of the volatility of the equity premium. A targeted subsidy that decreases diversification improves welfare by increasing managerial effort and reducing financial frictions
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; CAPM; Portfolio-Management; Anlageverhalten; Theorie; Consumption; Saving; Wealth; Portfolio Choice; Investment Decisions; Asset Pricing; Trading Volume; Bond Interest Rates; Financing Policy; Financial Risk and Risk Management; Capital and Ownership Structure; Value of Firms; Goodwill